Pengaruh Karakteristik Dewan Direksi dan Struktur Kepemilikan terhadap Corporate Social Responsibility Disclosure - Ni Luh Komang Dwi Ari Yudianti; I Gusti Ayu Desni Saraswati Sudirga (Jurnal Riset Akuntansi, 2026)
This study aims to examine the influence of board characteristics (educational background, tenure diversity, age diversity, and board size) and ownership structure (institutional ownership and foreign ownership) on Corporate Social Responsibility Disclosure. The theoretical basis for explaining the research findings is stakeholder theory and upper echelon theory. The data sample for this study is consumer sector companies, namely cyclical consumers and non-cyclical consumers listed on the Indonesia Stock Exchange in the 2021-2024 period, with a total of 368 observations. The sample determination used nonprobability sampling techniques and purposive sampling methods. Data analysis in this study was conducted using multiple linear regression methods with the assistance of the EViews 13 software. The results show that educational background and foreign ownership have no effect on CSR disclosure. Meanwhile, tenure diversity, age diversity, board size, and institutional ownership have a positive and significant effect on CSR disclosure. These findings support stakeholder theory, which emphasizes that companies are required to fulfill stakeholders’ information needs through transparent CSR disclosure. Furthermore, the research results also support the upper echelon theory which explains that the characteristics of the board of directors influence the company's strategic decision-making, including decisions related to CSR disclosure.